Consumer's webrooming conduct: an explanation using the theory of planned behavior. Issue 4 (10th September 2018) - Arora, Sourabh; Sahney, Sangeeta
Abstract : Purpose: Recent statistics concerning webrooming shoppers is indicative of the trending webrooming phenomenon, and points toward the dire need for the addressal of the issue. The purpose of this paper is to reason the consumer's intentional visit to an online store prior to making purchases offline by linking it with perceived channel benefits and uncertainty reduction approach through an application of the theory of planned behavior. Design/methodology/approach: A survey instrument was administered online, and a total of 374 responses were obtained. Respondents were queried with respect to the webrooming sequence, if at all they were into webrooming. The PLS-SEM was used to test the formulated hypotheses. Findings: The factor "Access to reviews online" emerged as the prime perceived search benefit which drives consumers' to first visit an online store, while factors like "access to touch and feel the product, " "better post-purchase services offline" and "immediate possession of product" induced customers to later purchase offline. Factors like "E-distrust" and "perceived risks related to purchasing online" notably determined consumer's movement to the physical store for purchasing the product in the second phase of the webrooming sequence. Research limitations/implications: A small sample size limits the authors from drawing definitive generalizations. Due to the lack of studies, individually examining webrooming conduct, a prior qualitative exploration can be conducted to draw more insights. Practical implications: The findings of the study can be utilized by the online retailers for devising strategies to push the webroomers to make purchases online. Social implications: The study creates awareness as to what motivates consumers to webroom, which has been realized as one of the serious issues being faced by the online retailers today. Originality/value: This study addresses a key concern "webrooming phenomenon, " which has emerged as a critical challenge in the present retailing dynamics.